2003
DOI: 10.1002/elps.200305437
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solvent on temperature and thermal peak broadening in capillary zone electrophoresis

Abstract: The present paper deals with the role of the solvent on thermal peak broadening. One main solvent property that determines the magnitude of the temperature gradient due to the generation of Joule heat in capillary zone electrophoresis is the thermal conductivity. As organic solvents have lower thermal conductivity than water (methanol and acetonitrile, e.g., nearly by a factor of 3) it can be hypothesized that the temperature gradient inside the capillary is more pronounced in organic solvents compared to an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 23 publications
0
34
1
Order By: Relevance
“…This treatment agrees with the classical approach to calculating the rise in temperature of the electrolyte adopted by Knox [12], Kok [18] and Porras et al [3], who assumed that a steady state is reached in which the rate at which heat is generated in the electrolyte is equal to the rate at which it is dissipated from the outer wall so that a constant temperature profile is achieved. Based on Eq.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…This treatment agrees with the classical approach to calculating the rise in temperature of the electrolyte adopted by Knox [12], Kok [18] and Porras et al [3], who assumed that a steady state is reached in which the rate at which heat is generated in the electrolyte is equal to the rate at which it is dissipated from the outer wall so that a constant temperature profile is achieved. Based on Eq.…”
Section: Introductionmentioning
confidence: 67%
“…DT Air is the difference in temperature between the external surface of the capillary wall and the temperature of the coolant T Set . Equation (3) shows how the power per unit length is calculated…”
Section: Introductionmentioning
confidence: 99%
“…The problem is not only the temperature increase itself but also the formation of an undesired temperature gradient. Several groups [119][120][121] proposed numerical solutions and models to alleviate Joule heat effects on EOF and mass transport. Sweedler's group [122] followed the change by nanoliter-volume NMR thermometry and concluded that the temperature change due to the Joule heating has a significant effect on highelectric-field and large-diameter channels.…”
Section: General Considerationsmentioning
confidence: 99%
“…It indicates that the WE system generates much more Joule heat, which is in direct ratio to the effective cross section area, A. If this Joule heat cannot be dispersed in time, excessive heat will result in a temperature gradient in the radial channel, and consequently cause serious problems, such as sample zone broadening [20][21][22] and, even worse, stopping the separation process. Therefore, the configuration of the shell-and-tube heat exchanger was introduced into the WE system to enhance the dispatching of heat in situ in real time.…”
Section: Resultsmentioning
confidence: 99%